PHYSICOCHEMICAL PROPERTIES OF SOME DRIED FISH PRODUCTS IN INDONESIA - Tri Winarni Agustini; Y. S. Darmanto; Eko Susanto (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Some traditional fish products in Indonesia have potential opportunity for global market, such as fish crackers, dried fish, ikan kayu (‘katsuobushi’) and dried pempek (traditional fish product from Palembang). Study on such products based on its glass transition temperature is still rare. On the other hand, glass transition phases of dried product play an important role in determining food stability because it can give an overview of physicochemical properties of the products. Using its glass transition temperature, dried fish product can be estimated for its shelf life. The purposes of this research are to observe the relation between some physicochemical properties of glass transition temperature of some dried fish products and its water content/water activity to the self life of the products. Dried fish products used were: fish cracker, dried-salted fish, ikan kayu (katsuobushi), fufu (very dried-smoked fish) and dried pempek. The samples were taken from different area in Indonesia (Cilacap, Palembang, and Sulawesi). The sample were taken using purposive sampling method. The method used for analysis of glass transition temperature was DSC method (Differential Scanning Calorimetry), and for water content and water activity were analysed using Aw meter and Moisture analyzer. All samples were analyzed in duplo. Research method used was experimental laboratory with research design of Completely Randomised Design. The experiment was conducted from August 2008 to December 2008 at Fish Product Processing Laboratory, Fisheries Department, Faculty of Fisheries and Marine Science – Diponegoro University, Food Engineering Laboratory – SQU, Oman. The results showed that different sample with different characteristics on physicochemical properties give different in water activity and also water content. The lowest water activity was performed by dried pempek. Glass transition temperature (Tg) of the products was very depend on the water content. The Tg of samples was ranged between 38.4oC – 76.4oC. The water content of the products ranged between 8.28%-37.28%. The Aw of the product was ranged between 0.57 – 0.87.